PIC Control Dc To Dc Converter With Variable Input Voltage And Constant Output Voltage For Photovoltaic Integration - Chan, Pui Weng (2012)
In recent years, attention towards renewable energy such as solar power had increased dramatically due to the awareness of energy crisis. A lot of solar power application systems had been designed. One of the most important solar power applications is to deliver the power produced by solar panel to local utility grid. A constant voltage should be obtained from solar panel in the design of this application system as solar panel is producing a fluctuating voltage level which depends on irradiation and temperature level. Therefore, a DC-DC boost converter is designed to step up the fluctuating solar panel voltage to a higher constant voltage. A microcontroller based DC-DC boost converter is proposed in this design. A PIC16F877 microcontroller is used and performs a voltage-feedback technique where it continuously tracks and measures the DC-DC boost converter output voltage and compares the measured value to a reference voltage. The differential compared value is used to produce a pulse-width-modulation signal. The signal is used to control a switch in the DC-DC boost converter. Simulation results describe the performance of the proposed design. Experimental work was carried out with the converter operating in continuous conduction mode with constant 24 V output voltage, 100 W output power, 20 kHz switching frequency and supplied from solar panel voltage. The experimental results show that the proposed design is able to produce a constant 24 V with efficiency more than 72.9% at 100 W load conditions.